2021
DOI: 10.1111/poms.13328
|View full text |Cite
|
Sign up to set email alerts
|

Network Size and Content Generation on Social Media Platforms

Abstract: Social media has been increasingly integrated into firm operations. Past literature documented the operational value of the content generated by social media users but paid little attention to the users’ incentives to generate and share content. We fill in the gap by linking a user’s social network to her content contribution. Specifically, we distinguish the role of the followee network (the group of people being followed by the user) from the role of the follower network. When a user follows more people, she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Third, the value of social information in operations and management, such as using social information to launch remedial actions in healthcare operations (Gour et al, 2022), predict retail sales (Cui et al, 2018), promote conversion and sales rates (Rong et al, 2022), and enhance the management Production and Operations Management of digital platforms (Lu et al, 2021, Wang et al, 2021, Wei et al, 2021Yan, 2020), has received significant attention in recent years. Our study contributes to this stream of research by the value of different types of social information in influencing contributors' performance.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, the value of social information in operations and management, such as using social information to launch remedial actions in healthcare operations (Gour et al, 2022), predict retail sales (Cui et al, 2018), promote conversion and sales rates (Rong et al, 2022), and enhance the management Production and Operations Management of digital platforms (Lu et al, 2021, Wang et al, 2021, Wei et al, 2021Yan, 2020), has received significant attention in recent years. Our study contributes to this stream of research by the value of different types of social information in influencing contributors' performance.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…Similarly, Moqri et al (2018) proposed that following others can increase the chance of a user's being exposed to useful information and, thus, increase contribution levels, but found the effect to be insignificant in the empirical analysis. Wei et al (2021) and Feng et al (2013), on the other hand, suggested that the behavior of followees decrease the contribution probability of a user because it becomes more difficult to synthesize information (information overload) and to provide valuable information (information redundancy). In the organizational context, Leonardi (2015) pointed out that employees can use the enterprise's social networking technology to observe the behavior of others and, thus, gain meta-knowledge (i.e., who knows what and who knows whom).…”
Section: Production and Operations Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, a Zhihu user can follow and be followed by other users. In this research, we name the user who follows another user in a following relation as the "follower" and the other party the "followee" [29]. The followee's activities on the site, e.g., posting and answering questions, will show up on the follower's news feed.…”
Section: Figure 1 the Screenshot Of A Profile Pagementioning
confidence: 99%
“…1 Similarly, in early 2020, Twitter started to flag what it judged to be inappropriate content related to COVID‐19. 2 Without proper quality control, the value of the platforms will be reduced (Choi et al., 2018; Cui et al., 2018; Wei et al., 2021; Yan & Pedraza‐Martinez, 2019). Hence, content screening will be one of the most crucial processes of the backend operations for platforms, especially those specializing in content provision.…”
Section: Introductionmentioning
confidence: 99%